2018
DOI: 10.1116/1.5022166
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the topography of uneven substrates post spin-coating

Abstract: The semiconductor industry has followed Moore's law for many decades and is currently preparing for high-volume manufacturing of the 7 nm technology node. To further scale down to the 5 nm technology node and below, research centers are constantly testing novel patterning and integration approaches. To enable a number of these new integration approaches, there is a growing need for a well-understood and well-controlled tone reversal technology. Tone reversal consists in inverting the tonality of all structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…Interestingly, we find that the deposited film is thinner both on the plateau and in the trench when the film is cast on a substrate featuring wide trenches than for similar plateau widths with narrower trenches (see Supplementary Table S1). This indicates that less material remains on the patterned area during spin coating when the plateaus are widely spaced, which is attributed to the influence of feature density, as has been previously reported [41,42]. Images of the deepest trench depths studied, 38 nm, show another interesting trend (Figure 5).…”
Section: Influence Of the Plateau And Trench Widthssupporting
confidence: 71%
See 4 more Smart Citations
“…Interestingly, we find that the deposited film is thinner both on the plateau and in the trench when the film is cast on a substrate featuring wide trenches than for similar plateau widths with narrower trenches (see Supplementary Table S1). This indicates that less material remains on the patterned area during spin coating when the plateaus are widely spaced, which is attributed to the influence of feature density, as has been previously reported [41,42]. Images of the deepest trench depths studied, 38 nm, show another interesting trend (Figure 5).…”
Section: Influence Of the Plateau And Trench Widthssupporting
confidence: 71%
“…This dependence becomes more accentuated for deeper trenches, which means that a deeper topography offers more versatility because their film profile changes over a larger range with the topographic feature density (as was observed for the 31 and 38 nm feature depths). Additionally, Figure 8d Decoster et al found a similar dependence (∆h = pd, where p quantifies the remaining topography after the 'planarization' of topographic features by the spin-coated material) [41]. Our analysis shows that with our PS-b-PMMA copolymer, the extent of planarization is at least 18.6% (for wide plateaus and/or trenches), and it further increases in a linear fashion with increasing density of topographical features (i.e., decreasing plateau and/or trench widths), where complete planarization is expected at wpl + wtr ≈ 115 nm (which is Decoster et al found a similar dependence (∆h = pd, where p quantifies the remaining topography after the 'planarization' of topographic features by the spin-coated material) [41].…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations